SERVICE FREQUENCY and SERVICE HOURS EVALUATION for BUS SERVICE in WEST KLANG VALLEY - Norhisham S.; Fadhlullah Abu Bakar M.; Hazwani Abd Samad Z.; Syamsir A.; Zaini N.; Yati Katman H.; Zakwan Ramli M. (Institute of Physics Publishing, 2023)
Bus transportation; Landforms; Bus services; Malaysian governments; Petaling; Public transport; Service frequency; Service Quality; Time interval; Waiting-time; Buses